PERINGKAT PENJAMIN EMISI, UNDERPRICING, DAN KINERJA PASAR SEKUNDER SAHAM IPO DI BURSA EFEK INDONESIA - Arni Utamaningsih (Jurnal Keuangan dan Perbankan, 2017)
This study discussed about the underwriters ranking, underpricing, and secondary market performance of IPOin Indonesia Stock Exchange. This study used the IPO prices, market prices, and data of underwriters rankingbased on the total value of transactions per year. The data were elaborated with standard deviation approach.These studies provided weak support on finding of Carter and Manaster (1990) that the higher the reputationof underwriter was, the lower the initial return was. This study elaborated the weak support. This study alsoproved that underpricing had positive and significant effect on the excess returns of 30 days. The evidence ofabnormal returns was elaborated for 30 days after the IPO.